Molecular characterization of novel transcription of antisense toxin-antitoxin RNA in regulating Mycobacterium tuberculosis - Dawson, Clinton C., author; Slayden, Richard A., advisor; Basaraba, Randall, committee member; Belisle, John, committee member; Karkhoff-Schweizer, RoxAnn, committee member; Tjalkens, Ronald, committee member (Colorado State University. Libraries, 2020)
Despite more than seventy years of available anti-tuberculosis (TB) treatments, Mycobacterium tuberculosis (Mtb) remains the deadliest human pathogen. Novel short-course therapies are needed that effectively treat latent TB infection (LTBI), which is like a major source for new infections. However, the molecular determinants of LTBI, including a large repertoire of regulators encoded by Mtb that mediate survival, are largely uncharacterized. Gene expression studies have implicated numerous regulators and particularly toxin-antitoxin (TA) systems in Mtb pathogenesis. Whole genome sequencing (i.e. WGS) studies have linked the massive genomic expansion of TA systems along with other pathogen-specific gene families to the emergence of TB-causing mycobacteria. In addition, a multitude of TA systems show genotypic differences that distinguish between ancient and modern lineages of Mtb. These predominantly include lineage-specific changes in amino acids, altering antitoxin DNA-binding, and nucleotides, generating new promoters. These mutations have led to an overrepresentation of differentially expressed Mtb TA genes responsible for mediating epigenetic changes that are associated with gains in virulence of modern lineages. Thus, the work presented in this dissertation begins to define the novel co-regulation of TA systems that underlie Mtb pathogenesis. Unraveling of more complex regulation of Mtb TA systems will provide keen insights into the phenotypic changes responsible for Mtb survival and persistence in vivo. This will ultimately help to streamline research and development of novel antibiotics as well as host directed immunotherapies against hard-to-treat tubercle bacilli, effectively shortening the duration of TB treatment. TA systems are ubiquitous among bacteria, especially pathogens, and increasingly found to be essential for adaptation to host immune defenses and in vivo drug pressures, resulting in the development of persistent or chronic infections. Phylogenomics comparisons have revealed that Mtb encodes a significantly expanded repertoire of TA systems that are solely conserved by tubercle bacilli, including homologous ParDE/RelBE systems like RelBE2 (i.e. Rv2865-Rv2866). Herein, we report a novel antisense (as)RNA, we call asRelE2, which is uniquely encoded by Mtb and involved in differentially post-transcriptionally regulating relE2 mRNA levels as part of the response to host-associated stress such as low pH in a cAMP-dependent manner. This dynamic regulation of the tripartite relBE2/asrelE2 TA locus appear to be essential for long-term survival under acidic stress in vitro. In addition, the overexpression of relE2 is found to mediate phenotypic development of a persistent state in Mtb associated with increasing tolerance towards frontline anti-TB drugs isoniazid (Inh) and rifampicin (Rif). In mice, asRelE2 acts in differentially regulating bi-cistronic relB2 and relE2 mRNA levels in a host tissue-specific manner dependent upon the downstream effector functions of interferon gamma (i.e. IFN-γ) in murine TB. Specifically, relE2 and relB2 mRNA levels are found to steadily increase in lungs and in spleens, respectively, in the development of the chronic phase of Mtb infection. To our knowledge, this is the first time a Mtb TA system has been shown to be co-regulated by an asRNA antitoxin. Furthermore, this is linked with the development of the adaptive host immune response to Mtb, demonstrating that the post-transcriptional regulation of TA systems is an important mechanism, coordinating the epigenetic changes that are a hallmark of Mtb persistence and pathogenesis.
Keywords: toxin-antitoxin systems; antisense RNA